Coassembly of Complementary Peptide Nucleic Acid into Crystalline Structures by Microfluidics. Issue 11 (28th July 2019) - Arnon, Zohar A.; Berger, Or; Aizen, Ruth; Hannes, Korren; Brown, Noam; Shimon, Linda J. W.; Gazit, Ehud
Abstract: The self‐assembly of simple units into well‐ordered supramolecular polymeric structures may give rise to a broad range of desirable attributes. In the field of bionanotechnology, there are two main classes commonly used as building blocks for self‐assembly—amino acids and nucleobases. While protein, peptide, and amino acid building blocks propose broad chemical versatility, the specific Watson–Crick base pairings of nucleic acids allow rational design and precise control over the assembly process. Specifically, artificially synthesized peptide nucleic acids (PNA), short DNA mimics that have an amide backbone, can present a unique set of properties while preserving the specific base pairing of the nucleic acids. The use of complementary building blocks allows the study of supramolecular polymer coassemblies. Here, the coassembly of two paired di‐PNA building blocks provides a new layer of control, as both building blocks are required for the spontaneous assembly to occur. Utilizing a microfluidic system, the growth of the well‐ordered structure can be regulated and monitored. The crystal structure of the formed assemblies display Watson–Crick base pairing with similar distances as those found in typical DNA double helices. Moreover, the crystals exhibit intriguing optical properties that may be implemented in various materials science and nanotechnological applications. Abstract : The specific Watson–Crick base pairing of peptide nucleic acids (PNA) governs their assembly into ordered structures. The use of complementary building blocks allows the study of supramolecular polymer coassemblies. Here, the controlled assembly of two paired di‐PNA building blocks is demonstrated using a microfluidics system to generate crystalline fluorescent structures.